Studi Potensi Industri Selulosa Nanokristalin dari Tandan Kosong Kelapa Sawit di Indonesia: Analisis SWOT dan Lokasi Pabrik - Senjawati , Maria Isfus; Maryam, Maryam; Akli, Khairul; Nadiyah, Khairun (Politeknik ATI Padang, 2025)
Oil palm empty fruit bunches (OPEFB), comprising 25-26% of fresh fruit bunches, contain up to 38.70% cellulose, making them a promising raw material for nanocrystalline cellulose (NCC) production. Bioprocess technology for producing NCC from OPEFB has been developed, with potential for industrial-scale application. This research analyzes potential factory locations for NCC production in the Sumbar-Riau region, Indonesia, using the value assessment method and complemented by SWOT, IFE, and EFE analyses. The assessment involved a team of 13 experts from the palm oil industry, including senior management from five different palm oil companies, who contributed to assessment through a Focus Group Discussion (FGD). The Kampar area in Riau was identified as the optimal location, scoring 82 out of 100, based on factors like raw material availability, market access, infrastructure, and labor. The SWOT analysis, supported by IFE (2.05) and EFE (2.65) scores, places Kampar in the S-O strategy quadrant, indicating a strong internal position and significant external opportunities. The recommended location in Kampar, with a production capacity of 2,000 tons/year, offers strategic advantages for NCC production. These results provide valuable insights for stakeholders, including investors, government, and industry, for developing the NCC industry in Indonesia, particularly in the Sumbar-Riau region.